Interactions between white pine blister rust, bark beetles, and climate over time indicate vulnerabilities to limber pine health - Burns, Kelly S.; Tinkham, Wade T.; Leddy, K. A.; Schoettle, Anna W.; Jacobi, William R.; Stewart, Jane E. (Frontiers in Forests and Global Change, 2023)
Limber pine (Pinus flexilis) is a keystone species in the Rocky Mountains, growing on harsh high elevation sites. The species is vulnerable to climate change and is challenged by the invasive disease, white pine blister rust (WPBR; Cronartium ribicola). Recently, outbreaks of native bark beetles have exacerbated these threats. Maintaining healthy limber pine is a concern for land managers. Information on health changes of these populations and long-term impacts is needed to guide management and restoration efforts with climate change. We established 106 long-term monitoring plots that were surveyed three times between 2004 - 2017 across 10 study areas. Density and basal area of live limber pine declined significantly, and mortality rates outpaced ingrowth rates. Limber pine health declined significantly with more than 20 percent of initially live limber pines dead by the last measurement cycle, primarily due to bark beetles and WPBR. Disease incidence and how it changed over time varied among study areas. Disease severity increased in all study areas, and most infected trees developed stem cankers. Limber pine regeneration was below average or absent in most sites and seedling mortality by WPBR increased significantly over time. Relationships between WPBR occurrence and severity progression with site, stand, and meteorological variables were modeled and suggest vulnerabilities of limber pine habitats to projected climate change. Trees in habitats with high vapor pressure deficit (more arid) had a lower likelihood of being infected with C. ribicola, but trees that were already infected were more likely to have an increase in disease severity and die. Longer growing seasons increased the likelihood of both C. ribicola being present and tree mortality. Vapor pressure deficit and growing season length tended to increase over the course of the study, suggesting that climate change may exacerbate disease impacts. Declining health of residual limber pine coupled with high mortality rates, increasing disease severity, and below average natural regeneration indicate successful recovery may not occur in some locations without management intervention. Proactive management strategies to reduce insect and disease impacts and promote stand recovery and resilience should be pursued in remaining, healthy limber pine ecosystems.